Pan-genômica do patógeno zoonótico negligenciado Bartonella henselae - Leandro Gomes Alves (2021)
The genus Bartonella is comprised of Gram-negative re-emerging bacteria like Bartonella henselae, which infects humans and survives inside erythrocytes. This species is transmitted by scratches and bites from domestic cats and usually causes a symptomatic infection in humans, known as Cat-Scratch Disease (CSD). The disease causes multiple clinical signs in humans, such as dermatic, cardiovascular, lymphatic, hepatic and nervous system diseases mainly in immunosuppressed individuals. Although the bacteria are highly relevant for its zoonotic importance worldwide, few studies aimed at characterizing these species genomes and there is still no pan-genome study available. Here, phylogenomic, pan-genome and genome plasticity analyses were performed to determine the epidemiological aspects, the size of the pan-genome and its variability in the identified pathogenicity islands. The 24 genomes of B. henselae analyzed showed similarity ranging from 96 to 100%. Two subsets of genomes were found in phylogenomic analyzes, one composed exclusively of strains isolated from cats and the other from feline and human hosts. A pan-genomic analysis identified 1655 non-redundant genes, where 70% of these genes integrate their core genome, composed of genes essential to the microorganism. In addition, the pan-genome development of the complete data set identified a α value = 0.94. The analysis of genomic plasticity revealed the presence of 6 pathogenicity islands and 1 phage region in the reference genome B. henselae Houston-1. Overall, the results showed that the genomes are highly similar, with a pan-genome tending to become closed. Furthermore, the regions of genomic plasticity analyzed are composed of genes related to the virulence of the bacteria. For the validation of genomic distribution patterns, the need of sequencing more genomes worldwide is pointed out in order to better characterize the variations in the pan-genome and understand the adaptation patterns of this species. The high conservation of genomes of this species is very important for the development of new vaccines and analyzes of drug targets against this pathogen. These data can be used in future works, of great relevance for the containment of the disease worldwide.